GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 2919 species occurrences available in GBIF matching the query: TaxonKey: Andrena cressonii Robertson, 1891. The dataset includes 2919 records from 13 constituent datasets: 507 records from Bee Biology and Systematics Laboratory. 1 records from Lund Museum of Zoology - Insect collections (MZLU). 4 records from Hymenoptera specimen database of Kyushu University. 40 records from Museum of Comparative Zoology, Harvard University. 12 records from Bees of Canada / Gschwendtner property collection. 1016 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 1283 records from Illinois Natural History Survey Insect Collection. 18 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 6 records from NMNH Extant Specimen and Observation Records. 20 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 3 records from Entomology Division, Yale Peabody Museum. 3 records from Snow Entomological Museum Collection. 6 records from UCMC_Entomology. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences